Impact of home food production on nutritional blindness, stunting, wasting, underweight and mortality in children: a systematic review and meta-analysis of controlled trials. Issue 7 (12th April 2022) - Bassey, Chizoba; Crooks, Harriet; Paterson, Katherine; Ball, Rachel; Howell, Kristoffer; Humphries-Cuff, Iona; Gaffigan, Kirsty; Rao, Nitya; Whitty, Jennifer A.; Hooper, Lee
Abstract: Vitamin A deficiency is highly prevalent and remains the major cause of nutritional blindness in children in low-and middle-income countries, despite supplementation programmes. Xeropthalmia (severe drying and thickening of the conjunctiva) is caused by vitamin A deficiency and leads to irreversible blindness. Vitamin A supplementation programmes effectively reduce vitamin A deficiency but many rural children are not reached. Home food production may help prevent rural children's vitamin A deficiency. We aimed to systematically review trials assessing effects of home food production (also called homestead food production and agricultural interventions) on xeropthalmia, nightblindness, stunting, wasting, underweight and mortality (primary outcomes). We searched Medline, Embase, Scopus, Cochrane CENTRAL and trials registers to February 2019. Inclusion of studies, data extraction and risk of bias were assessed independently in duplicate. Random-effects meta-analysis, sensitivity analyses, subgrouping and GRADE were used. We included 16 trials randomizing 2498 children, none reported xerophthalmia, night-blindness or mortality. Home food production may slightly reduce stunting (mean difference (MD) 0.13 (z-score), 95% CI 0.01 to 0.24), wasting (MD 0.05 (z-score), 95% CI −0.04 to 0.14) and underweight (MD 0.07 (z-score), 95% CI −0.01 to 0.15) in young children (all GRADE low-consistency evidence), and increase dietary diversity (standardized mean difference (SMD) 0.24, 95% CI 0.15 to 0.34). Home food production may usefully complement vitamin A supplementation for rural children. Large, long-duration trials with good randomization, allocation concealment and correct adjustment for clustering are needed to assess effectiveness of home food production on nutritional blindness in young children.